Regularity of the mild solution of a parabolic equation with stochastic measure - Bodnarchuk, I. M. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
We study a stochastic parabolic differential equation driven by a general stochastic measure. The existence, uniqueness,and Holder regularity of the mild solution are established.